Optimum dietary protein requirement of striped murrel Channa striatus fry - D, Kumar.; K., Marimuthu.; M.A, Haniffa.; T.A, Sethuramalingam. (Malaysian Journal of Science, 2010)
This article deals with the dietary requirement of protein of Channa striatus fry, five different semi moist diets were formulated separately using semi purified ingredients (chicken intestine, fish waste and silk worm pupae). The highest specific growth rate (1.613%/day), food conversion ratio (1.526) weight gain (267.21%) average daily growth rate (0.824 %) and survival (96.66%) for fry were recorded in 55% of protein diet. Similarly carcass composition of fry differed according to the different protein levels. (Key words: Channa striatus fry, nutrition, growth, survival)